Bias in Machine Learning Algorithms - Sharma, Indrani; Rathodiya, Bhimraj (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Bias in machine learning algorithms has emerged as a critical concern, casting a shadow on the perceived objectivity and fairness of these systems. This paper delves into the multifaceted landscape of biases inherent in machine learning models, exploring their origins, manifestations, implications, and potential remedies. The investigation begins by elucidating the sources of bias, stemming from various stages of the machine learning pipeline, including data collection, feature selection, algorithmic design, and human interventions. It unravels how biases, whether implicit in historical data or inadvertently introduced, can perpetuate societal inequalities, reinforce stereotypes, and result in discriminatory outcomes. The paper examines the manifestations ofbias in different domains, such as healthcare, criminal justice, finance, and employment, where machine learning algorithms wield substantial influence. It highlights instances where biased models can lead to unequal treatment, exacerbating societal disparities and compromising ethical standards. Moreover, the study explores the challenges associated with detecting, measuring, and mitigating bias in machine learning algorithms. It navigates through various fairness metrics, algorithmic transparency techniques, and debiasing strategies aimed at promoting fairness, accountability,and transparency in algorithmic decision-making. In addition to uncovering the intricacies of bias, this paper underscores the ethical imperatives in mitigating bias, emphasizing the need for interdisciplinary collaboration,ethical guidelines, and regulatory frameworks. It advocates for a holistic approach that amalgamates technical advancements with ethical considerations to steer machine learning algorithms toward equitable and socially responsible outcomes. In conclusion, bias in machine learning algorithms represents a multifaceted challenge, necessitating a concerted effort from researchers, policymakers, and practitioners. Addressing bias requires not only technical innovations but also ethical scrutiny, transparency, and a commitment to promoting fairness and inclusivity in algorithmic systems. This abstract provides an overview of the multifaceted nature of bias in machine learning algorithms, exploring its origins, implications, challenges, and the necessity for a holistic approach encompassing technical and ethical considerations.